2020
DOI: 10.7475/kjan.2020.32.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Patient Activation on Diabetes Self-Care Activities and Diabetes-Specific Distress

Abstract: The purpose of the study was to evaluate the influence of patient activation on diabetes self-care activities and diabetes-specific distress among patients with type 2 diabetes mellitus. Methods: This cross-sectional correlational study was a secondary data analysis, utilizing data collected from September 2016 to July 2017, for 151 adults diagnosed with type 2 diabetes in ambulatory endocrinology units of two tertiary hospitals in a metropolitan city. The instruments used for data collection included the Summ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
0
0
1
Order By: Relevance
“…Keum et al [29] reported that diabetes distress increases with age, but there was no difference in diabetes distress according to age in this study. Similar to this study, the subjects in Choi and Kim [30] had a shorter duration of illness compared to the subjects in Keum et al [29]. This suggests that diabetes distress in people with diabetes is influenced more by disease-related characteristics than by age.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Keum et al [29] reported that diabetes distress increases with age, but there was no difference in diabetes distress according to age in this study. Similar to this study, the subjects in Choi and Kim [30] had a shorter duration of illness compared to the subjects in Keum et al [29]. This suggests that diabetes distress in people with diabetes is influenced more by disease-related characteristics than by age.…”
Section: Discussionsupporting
confidence: 85%
“…The diabetes distress score exceeded the average of 2.30 points in a similar study conducted by Keum et al [29] utilizing the same assessment tool. However, although Choi and Kim [30] did not use the same tools, the results were similar to their findings, where the diabetes distress level of patients with diabetes was 6.91 points (out of 12 points). Keum et al [29] reported that diabetes distress increases with age, but there was no difference in diabetes distress according to age in this study.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The participants displayed effective outcomes with regard to DM control. For example, the HbA1c was 7.5 ± 1.5%, performing lower than that reported in previous studies [79,80]. In addition, over 90% of the participants controlled their glucose with oral medication.…”
Section: Discussioncontrasting
confidence: 64%
“…Quanto às pessoas que não faziam dieta hipoglicemiante e nem exercício físico, uma investigação realizada na Coreia ratifica os achados desta pesquisa, pois mostra que quando os indivíduos não fazem nem uma atividade nem outra, demonstram negatividade em relação à adesão aos demais cuidados, e quando ocorre o contrário, as pessoas realizam melhor o autocuidado, principalmente àqueles relacionados com a adesão à terapia medicamentosa e aos cuidados com os pés (15) . Sabe-se que a alimentação adequada, principalmente em indivíduos diabéticos, colabora para o controle glicêmico e ganho de peso ideal (16) .…”
Section: Discussionunclassified